2021
DOI: 10.1002/hec.4266
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana legalization and household spending on food and alcohol

Abstract: Utilizing the Consumer Expenditure Interview Survey from 2005 to 2019, I study spending on food and alcohol following recreational marijuana law (RML). Exploiting differences in the timing of the passage of RMLs and employing two-way fixed-effects methods, I find that households located in states adopting these laws increase their quarterly spending on food, which is driven mainly by spending on food consumed away from home. Legalization of recreational marijuana also leads to increased quarterly spending on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A series of seven articles investigated the association between recreational cannabis legalization and alcohol use. Three studies provide evidence for an increase in alcohol consumption in RML states, as reported by the Consumer Expenditure Interview Survey ( 42 ), HCUP data ( 33 ), and the ACHA-National College Health Assessment II (NCHA-II) ( 23 ), across RML states. Curiously, 3 studies failed to show an association between legalization and alcohol use ( 24 , 27 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…A series of seven articles investigated the association between recreational cannabis legalization and alcohol use. Three studies provide evidence for an increase in alcohol consumption in RML states, as reported by the Consumer Expenditure Interview Survey ( 42 ), HCUP data ( 33 ), and the ACHA-National College Health Assessment II (NCHA-II) ( 23 ), across RML states. Curiously, 3 studies failed to show an association between legalization and alcohol use ( 24 , 27 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…RCL may lead to an increase in alcohol, tobacco and other substance use. A study using the Consumer Expenditure Interview Survey found that households in RCL states increased their spending on food and alcohol, indicating a connection between cannabis, food and alcohol use [38]. Three studies using the US Behavioral Risk Factor Surveillance System and YRBS data found a significant association between RCL with increased alcohol use, primarily among younger adults and men [39], electronic vapor product use (''vaping''), cannabis, and cigarette use [40] and a small increase in the likelihood of any e-cigarette use among adolescents [41].…”
Section: Other Substance Usementioning
confidence: 99%